A Psychoanalytic Analysis of Obsession for Perfection and Psychological Unravelling in Black Swan (2010) - Mahira Fadhila; Much Raihan Chanief; Sang Ayu Made Chandra Dinda Galung; Sania Lea Kristina; Satria Jati Pangestu Putra; Rina Saraswati; Rizal Octofianto Datau (Pusat Riset dan Inovasi Nasional, 2024)
Black Swan (2010) is a psychological horror movie that explores themes of ambition, perfectionism, and the psychological toll of obsession in the competitive world of professional ballet. The movie delves into Nina's descent into madness as she strives for artistic perfection, blurring the lines between reality and hallucination. The aim achieved in this analysis includes examining how psychological stress manifests itself, how high-pressure artistic circumstances can distort reality, and how these factors influence the protagonist's spiral toward mental instability. This is qualitative-descriptive research. The researchers follow a four-step process involving data identification, classification, analysis, and concluding. The main data collection comes from Black Swan (2010), focusing on scenes when Nina Sayers experiences mental breakdowns. The researchers collected data from the film itself and several journals, focusing on Nina's mental disorders and applying Freudian concepts to analyze her behavior and personality. The research results show that obsession and strong demands for perfection from herself and others have disturbed Nina's mental instability in Black Swan (2010).